Report on the 1992 stock assessment of the Wyre catchment - Walsingham, M.V. (National Rivers Authority North West, 1993)
The aim of this study was to assess the status of the juvenile salmonid and coarse fish populations of the Wyre catchment. Emphasis was placed on an examination of the distribution of spawning and nursery areas for salmonids within the study area and an assessment of the status of juvenile salmonid stocks. The species distribution and spawning areas for other fish species were also identified where possible and the status of the Wyre coarse fishery, downstream of Churchtown Weir, assessed. This report examines the results of stock assessment surveys carried out in the Wyre catchment between 2/06/92 and 11/08/92. Forty-six sites were surveyed from Tarnbrook Wyre (SD. 598577) and Marshaw Wyre (SD. 614541) downstream to St Michaels (SD. 465411). Flow, habitat and in-river obstructions have been shown to affect juvenile salmonid densities. A habitat description is provided for each site studied during the course of this study. Environment Agency Archives North West